Linezolid use for the treatment of multidrug-resistant tuberculosis, TB centers of excellence, United States, 2013–2018. (February 2021) - McDowell, Ashley; Haas, Michelle; Seaworth, Barbara; Wilson, John W.; Patrawalla, Amee; Haley, Connie; Lauzardo, Mike; de Bruyn, Miko; Goswami, Neela D.
Abstract: Background: In 2019, the World Health Organization released guidelines reflecting major changes in multidrug-resistant tuberculosis (MDR-TB) management—prioritizing fluoroquinolones, bedaquiline, and linezolid (LZD) while de-emphasizing previously favored injectable agents. In some cases, linezolid use is associated with gastrointestinal intolerance, mitochondrial toxicity, and significant drug interactions. CDC's Division of Tuberculosis Elimination supports a network of regional TB Centers of Excellence, which provide medical consultation to healthcare providers. Consultations are documented in a medical consultation database (MCD) enabling evaluation of management questions and recommendations. We describe the scope of clinical inquiries and responses specific to linezolid use for MDR-TB in the US. Research Question: What are the major themes of provider and patient challenges regarding the use of linezolid for the treatment of MDR-TB in the US? Methods: We queried MCD consults categorized as "MDR/XDR-TB" from 1/1/2013 to 12/31/2018. Only linezolid-specific consultations were included; incomplete and duplicate entries were excluded as were those citing linezolid historically or theoretically. Subgroup characteristics were assessed (e.g., Center, year, provider type). A descriptive coding scheme was developed through inductive thematic analysis. Results: In 2013–2018 of the 1889 consults regarding MDR/XDR-TB, 934 MDR-TB consults referenced linezolid; 137 met inclusion criteria, representing between 4 and 10% of MDR-TB consults annually. Four main themes emerged: adverse effects (71.5%); concerns about linezolid use due to co-morbidities or concurrent medication use (15.3%); dosing adjustments (8.8%); and monitoring and maintenance logistics (4.4%). Interpretations: Linezolid consults consistently exceeded 4% of all consults annually over the 6-year period, suggesting a need for access to expert opinion for providers using linezolid to manage MDR-TB. While only a snapshot of MDR-TB in the US, this evaluation summarizes major provider concerns regarding particular adverse effects, and highlights a need for evidence-based guidance regarding linezolid dosing and toxicity management.